Comprehensive Benchmarking of Message Brokers: Evaluating Performance and Security Metrics for Reliable Messaging Systems - Putra, Sipky Jaya; Firmansyah, Gerry; Tjahjono, Budi; Akbar , Habibullah (Riviera Publishing, 2025)
A message broker plays a crucial role in distributed communication systems by ensuring reliable message delivery between services. In practice, choosing a message broker involves not only considering performance aspects such as latency and throughput but also security features like authentication, authorization, and encryption. However, challenges arise when enhancing security layers negatively impacts system performance. This study aims to explore and evaluate four popular message brokers—Apache Kafka, Apache Pulsar, Apache RocketMQ, and RabbitMQ—focusing on performance metrics (latency and throughput) across various security configuration levels (no security, TLS, basic authentication, and advanced authentication). The evaluation is conducted through standardized benchmarking processes to assess the impact of security feature implementation on overall system performance. The results of this research are expected to provide insights into the optimal balance between security and performance that remains acceptable by industry standards. Furthermore, the findings may assist developers and system architects in selecting the most suitable message broker configuration based on scalability requirements and data sensitivity levels.